Association Between Use of Traditional Chinese Medicine Herbal Therapy and Survival Outcomes in Patients With Stage II and III Colorectal Cancer: A Multicenter Prospective Cohort Study. Issue 52 (13th November 2017) - Xu, Yun; Mao, Jun J; Sun, Lingyun; Yang, Lin; Li, Jie; Hao, Yingxu; Li, Huashan; Hou, Wei; Chu, Yuping; Bai, Yu; Jia, Xiaoqiang; Wang, Jinwan; et al.
Abstract: Background: Chinese cancer patients often use Traditional Chinese Medicine (TCM) herbal medicine during or after active cancer treatments. However, little is known about how TCM herbal medicine impacts cancer outcomes. This study aimed to evaluate the association between TCM herbal therapy and survival outcomes in patients with stage II or III colorectal cancer. Methods: We conducted an eight-center prospective cohort study in China among patients who had undergone radical resection for stage II and III colorectal cancer. All patients received comprehensive conventional treatments according to National Comprehensive Cancer Network (NCCN) guidelines, and follow-up visits were conducted over five years. We defined high exposure as a patient's use of TCM individualized herbs for more than one year, ascertained via clinical interviews. The primary outcome was disease-free survival (DFS), with overall survival (OS) as a secondary outcome. Results: Between April 2007 and February 2009, we enrolled 312 patients into the cohort; 166 (53.2%) met the definition of high exposure to TCM herbs. Adjusting for covariates, high exposure to TCM was associated with both better DFS (hazard ratio [HR] = 0.62, 95% confidence interval [CI] = 0.39 to 0.98) and OS (HR = 0.31, 95% CI = 0.14 to 0.68). In subgroup exploratory analysis, the effects demonstrated that the differences in outcomes were statistically significant in patients who had received chemotherapy. Conclusion: Longer duration of TCM herbal use is associated with improved survival outcomes in stage II and III colorectal cancer patients in China. More research is needed to evaluate the effects and underlying mechanisms of herbal medicine on colorectal cancer outcomes.